2008
DOI: 10.1063/1.2902805
|View full text |Cite
|
Sign up to set email alerts
|

Piezoelectric and ferroelectric properties of Bi-compensated (Bi1/2Na1/2)TiO3–(Bi1/2K1/2)TiO3 lead-free piezoelectric ceramics

Abstract: Multiferroic response of nanocrystalline lithium niobate J. Appl. Phys. 111, 07D907 (2012) Non-radiative complete surface acoustic wave bandgap for finite-depth holey phononic crystal in lithium niobate ͑Bi 1/2 Na 1/2 ͒TiO 3 -͑Bi 1/2 K 1/2 ͒TiO 3 ͑BNT-BKT͒ ceramics as a promising candidate for lead-free piezoelectric ceramics were studied with a special emphasis on the compositional dependence of piezoelectric and ferroelectric properties. One mole percent excess Bi was added to compensate for the volatilizati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
40
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(45 citation statements)
references
References 28 publications
5
40
0
Order By: Relevance
“…The tan δ values are all approximately 0.04 at 1 MHz, which is still higher than that required for practical applications. The number of grain boundaries was increased in the SrTaO 2 N-Sr/La bulks due to the smaller grain size, leading to an accumulation of the space charge [33]. This may be one reason for the high dissipation factor.…”
Section: Methodsmentioning
confidence: 99%
“…The tan δ values are all approximately 0.04 at 1 MHz, which is still higher than that required for practical applications. The number of grain boundaries was increased in the SrTaO 2 N-Sr/La bulks due to the smaller grain size, leading to an accumulation of the space charge [33]. This may be one reason for the high dissipation factor.…”
Section: Methodsmentioning
confidence: 99%
“…3 Proposed alternatives to lead-based piezoelectric ceramics include BaTiO 3 (BT), (K,Na)NbO 3 (KNN), (Bi,Na)TiO 3 (BNT), (Ba,Ca)(Ti,Zr)O 3 (BCTZ), (Ba,Ca)(Ti,Sn)O 3 (BCTS), and (Ba,Ca) (Ti,Hf)O 3 (BCTH). [4][5][6][7] Some researchers have reported that BCTZ and BCTS ceramics can potentially replace lead-based piezoelectric ceramics because of their high piezoelectric properties. The morphotropic phase boundary (MPB) in PZT ceramics has extremely high dielectric, ferroelectric, and piezoelectric properties, which are caused by enhanced polarizability due to coupling between equivalent energy states of ferroelectric tetragonal (T) and ferroelectric rhombohedral (R) phases, making domain switching easy.…”
Section: Introductionmentioning
confidence: 99%
“…For its relatively large remanent polarization (P r 038 μC/cm 2 ) at room temperature and high Curie temperature (T c 0320°C), BNT has been considered to be a good candidate for lead-free piezoelectric ceramics. However, for pure BNT, it is difficult to pole due to high coercive field (E c 073 kV/cm) and high conductivity, which will make its piezoelectric and pyroelectric properties much lower than PZT ceramics [3]. To improve the piezoelectric and pyroelectric properties of the material, a number of BNT-base solid solutions, such as BNT-BaTiO 3 , BNT-Bi 0.5 K 0.5 TiO 3 , BNT-NaNbO 3 , BNT-KNbO 3 , BNT-Bi 0.5 K 0.5 TiO 3 -Bi 0.5 Li 0.5 TiO 3 and BNT-Bi 0.5 K 0.5 TiO 3 -BaTiO 3 have been studied extensively [4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%